Directional Polarimetric Camera (DPC): Monitoring aerosol spectral optical properties over land from satellite observation. (October 2018) - Li, Zhengqiang; Hou, Weizhen; Hong, Jin; Zheng, Fengxun; Luo, Donggen; Wang, Jun; Gu, Xingfa; Qiao, Yanli
Highlights: The DPC onboard GF-5 is introduced and aerosol retrieval capabilities are evaluated. An inversion framework by taking full advantage of DPC measurements is developed. An improved BRDF model is used to reduce the inversion complexity of surface. Aerosol spectral optical parameters can be well retrieved over various conditions. Abstract: The Directional Polarimetric Camera (DPC) is the first Chinese multi-angle polarized earth observation satellite sensor, which will be launched onboard the GaoFen-5 Satellite in Chinese High-resolution Earth Observation Program. GaoFen-5 runs in a sun-synchronous orbit with an inclination angle of 98°, with the 13:30 PM local overpass time and the 2-days revisiting period. DPC employed a charge coupled device detection unit with 512 × 512 effective pixels from the 544 × 512 useful pixels, realizing spatial resolution of 3.3 km under a swath width of 1850 km. Meanwhile, DPC has 3 polarized channels (490, 670 and 865 nm) together with 5 non-polarized bands (443, 565, 763, 765 and 910 nm), and can obtain at least 9 viewing angles by continuously capturing series images over the same target on orbit. Based on the optimal estimation theory and improved bidirectional reflectance distribution function model, an inversion framework for the simultaneous retrieval of aerosol and surface parameters is presented by taking full advantage of available radiometric and polarimetric measurements. The retrieved wavelength-independent fine-mode and coarse-mode aerosol volumes are used to assess the DPC performance on the inversion capability of spectral aerosol optical depth (AOD), from which the Angstrom exponent and fine-mode fraction (FMF) could be further obtained. In addition, based on the synthetic DPC data for various observation geometries, aerosols and surface types, the aerosol inversion capabilities are systematically evaluated, and the information content analysis results show that the aerosol spectral optical properties can be well retrieved over various land surfaces.